Modeling and performance analysis of a vehicle with kinetic dynamic suspension system. (February 2019) - Yang, Wu; Nong, Zhang; Bangji, Zhang; Jie, Zhang
This paper presents a kinetic dynamic suspension (KDS) system to achieve enhanced cooperative control of the roll and warp motion modes for on-road and off-road sports utility vehicles (SUV). The proposed KDS system consists of two hydraulic circuits acting on two pairs of torsional rods and levers, which can be treated as novel anti-roll bars. Hence, these anti-roll bars do not work independently, but are coupled to merely respond to particular motion modes. To verify the handling and ride performance of the system, a 14-DOF model of a SUV and a "magic formula" tire model are developed. The dynamic responses of the vehicle model with KDS suspension are obtained through half-sine bump, asynchronous sine road, and fishhook maneuver simulations. The responses of the KDS equipped vehicle are compared to those of one with anti-roll bars to demonstrate its improved performance and also illustrate the side-effects. The results show that the KDS system considerably improves the vehicle's anti-roll ability. Furthermore, the vehicle's warp stiffness is significantly reduced by the KDS system, which enhances the vertical load distribution of each wheel when driving off-road.